2018
DOI: 10.1002/anie.201804531
|View full text |Cite
|
Sign up to set email alerts
|

Inside Back Cover: Transient and Persistent Room‐Temperature Mechanoluminescence from a White‐Light‐Emitting AIEgen with Tricolor Emission Switching Triggered by Light (Angew. Chem. Int. Ed. 22/2018)

Abstract: Persistent luminescence … …from purely organic materials was triggered by mechanical force at room temperature for the first time.Intheir Communication on page 6449 ff., B. Xu, G. Shi, and co-workers show that aw hite-light-emitting AIEgen exhibited not only persistent photoluminescence,but also transient and persistent room-temperature mechanoluminescence (ML). By simply turning on and off the exciting UV light, tricolor emission switching between blue,white,and yellow was also achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, crystallization also have facilitated more channels for ISC than their monomers, leading to an enhancement in the RTP efficiency. [ 63 ] Huang's group focuses on a quantitative investigation about the relationship of aggregation and RTP properties based on aggregation engineering by varying the position and number of CN substituents of cyanophenyl carbazoles. [ 64 ] It is found that thermally activated reversed phase transformation H‐aggregation plays a key role in the splitting energy (Δε) and the RTP emission.…”
Section: Aggregation‐induced Rtp For Afterglow Imagingmentioning
confidence: 99%
“…In addition, crystallization also have facilitated more channels for ISC than their monomers, leading to an enhancement in the RTP efficiency. [ 63 ] Huang's group focuses on a quantitative investigation about the relationship of aggregation and RTP properties based on aggregation engineering by varying the position and number of CN substituents of cyanophenyl carbazoles. [ 64 ] It is found that thermally activated reversed phase transformation H‐aggregation plays a key role in the splitting energy (Δε) and the RTP emission.…”
Section: Aggregation‐induced Rtp For Afterglow Imagingmentioning
confidence: 99%
“…In 2001, Tang and coworkers 22 discovered a special kind of molecule displaying an aggregation-induced emission (AIE) phenomenon, which meant molecules were nonemissive at the monomeric state while exhibiting bright fluorescence at the aggregation state. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Electron-donating (D) and -accepting (A) units are often embedded into AIE-gens for triggering polarityresponsive emission changes assisted by the twisted intramolecular charge transfer (TICT) effect. 43,44 On the basis of this special effect, we prepared a kind of AIE hydrogel, which then displayed continuous gradient fluorescence after being immersed in organic solvents based on a polar-responsive AIE-gen (Scheme 1A, right).…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Tang and coworkers 22 discovered a special kind of molecule displaying an aggregation‐induced emission (AIE) phenomenon, which meant molecules were nonemissive at the monomeric state while exhibiting bright fluorescence at the aggregation state 23–42 . Electron‐donating (D) and ‐accepting (A) units are often embedded into AIE‐gens for triggering polarity‐responsive emission changes assisted by the twisted intramolecular charge transfer (TICT) effect 43,44 .…”
Section: Introductionmentioning
confidence: 99%